2008
DOI: 10.1007/s11130-008-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Protection by Noni Fruit Juice Against CCl4-Induced Chronic Liver Damage in Female SD Rats

Abstract: Morinda citrifolia L. (noni) has been used throughout the Pacific, Southeast Asia, Central America, and the Caribbean for a variety of health conditions, including heart and liver ailments. In this study, we examined the hepatoprotective effects of TAHITIAN NONI Juice (TNJ) against CCl(4)-induced chronic liver damage in female Sprague Dawley (SD) rats. Twelve female SD rats were divided into control, placebo and TNJ (6 mL/rat/day) groups. On day 15, animals in the placebo and TNJ groups received 0.25 mL/kg CCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 28 publications
(24 reference statements)
7
43
0
2
Order By: Relevance
“…4c) levels were elevated in EAC control cluster which indicates that EAC cells induce hepatotoxicity. Reduction in the above biochemical markers levels by dint of NJ and DNG respectively in CP challenged mice indicates that NJ and DNG correspondingly possesses the protective effect against EAC cell induced hepatotoxicity this result is correlated with Wang et al, 37 who were demonstrated that hepatoprotective activity of fermented NJ against CCl 4 induced liver injury. Exhibited above myeloprotective and hepatoprotective properties of NJ and DNG may be due to the antioxidant activity of their phenolic and flavonoids compounds.…”
Section: Fig 4: Alt Concentration (U/l) (4a) Ast Concentration (U/lsupporting
confidence: 65%
“…4c) levels were elevated in EAC control cluster which indicates that EAC cells induce hepatotoxicity. Reduction in the above biochemical markers levels by dint of NJ and DNG respectively in CP challenged mice indicates that NJ and DNG correspondingly possesses the protective effect against EAC cell induced hepatotoxicity this result is correlated with Wang et al, 37 who were demonstrated that hepatoprotective activity of fermented NJ against CCl 4 induced liver injury. Exhibited above myeloprotective and hepatoprotective properties of NJ and DNG may be due to the antioxidant activity of their phenolic and flavonoids compounds.…”
Section: Fig 4: Alt Concentration (U/l) (4a) Ast Concentration (U/lsupporting
confidence: 65%
“…Previous studies have demonstrated the antioxidant activities of arbutin (41). Lipid peroxidation has been involved in the pathogenesis of hepatic injury by free radical derivatives of CCl 4 and is responsible for cell membrane damage and the subsequent release of marker enzymes of hepatotoxicity (22,40,42). In the present study, significantly elevated levels of TBARS, the product of membrane lipid peroxidation observed in CCl 4 -administered rats, indicated hepatic damage.…”
Section: Discussionsupporting
confidence: 51%
“…Pretreatment with arbutin significantly improved the structure of hepatic cells. These results suggest that arbutin is effective at reversing the hepatotoxicity caused by CCl 4 . Morphometric studies have confirmed these observations.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Therefore, in most experimental animal models especially inducing liver injury, the LFT is the well-known parameter to measure activity of liver enzyme (Wang, et al, 2008).…”
mentioning
confidence: 99%